The Legal Aspects of Cybercrime in Nigeria: An Analysis with the UK Provisions - Ibekwe, Chibuko Raphael (2015)
Cybercrime offences know no limits to physical geographic boundaries and have continued to create unprecedented issues regarding to the feasibility and legitimacy of applying traditional legislations based on geographic boundaries. These offences also come with procedural issues of enforcement of the existing legislations and continue to subject nations with problems unprecedented to its sovereignty and jurisdictions. This research is a critical study on the legal aspects of cybercrime in Nigeria, which examines how laws and regulations are made and applied in a well-established system to effectively answer questions raised by shortcomings on the implementation of cybercrime legislations, and critically reviews various laws in Nigeria relating or closely related to cybercrime. This research will provide insight into current global cybercrime legislations and the shortfalls to their procedural enforcement; and further bares the cybercrime issues in Nigeria while analysing and proffering a critique to the provisions as provided in the recently enacted Nigerian Cybercrime (Prohibition and Prevention) Act 2015, in contradistinction to the existing legal framework in the United Kingdom and the other regional enactments like the Council of Europe Convention on Cybercrime, African Union Convention on Cybersecurity and Personal Data Protection 2014, and the ECOWAS Directive on Cybercrime 2011